Modelo alométrico para estimar la altura total de las especies forestales del bosque de colina baja de la concesión forestal 16-LOR-MAY/CON-MAD-2017-055, distrito de Mazán, Loreto, 2022 - Paima Roque, Amador Rody (2023)
The allometric model was determined to estimate the total height of low hill forest species of forest concession 16-LOR-MAY/CON-MAD-2017-055, Mazánn district, Loreto, Peru. The forest census data of commercial species of the operational plan (OP) 1 of the cutting plot PC 8 for forest harvesting permits was evaluated. The results indicate that a total of 660 trees were recorded, grouped into 29 commercial forest species and 15 botanical families. The average diameter-to-total height relationship of the trees was fitted to the power-type distribution model (Y= 33,482 x DBH 0,105), with a correlation coefficient of r=0,942 and a coefficient of determination of R2=0,886. The hypothesis is rejected in the sense that the linear allometric model did not fit the diameter-to-total height relationship to estimate the height of trees in the low hill forest.